Cyclostationary Near-field Acoustic Holography for Gearboxes - Zhu Song; Zhang Erliang; Gao Xiaoyu (Jixie chuandong)
Regarding the problem that the traditional near-field acoustic holography (NAH) has difficulty in reconstructing the sound field of the gearbox, this work makes full use of the cyclostationary characteristics of the radiated noise and combines the cyclostationary signal analysis with the equivalent source NAH algorithm to develop a sound imaging method for the gearbox. Firstly, the set of cyclic frequencies was estimated from the noise signal; secondly, the cyclic frequency of interest was selected, and the corresponding cyclic spectral density function was calculated; thirdly, the equivalent source NAH method was developed to reconstruct the potential sound source of the gearbox. Finally, the effectiveness of the sound imaging method was justified by the simulation and experimental data.